Splenic Mass and its Relation to Age Sex and Height of the Individual in Bangladeshi Peoples - Khalil, Mohsin; Chowdhury, Md Ashraful Islam; Rahman, Habibur; Mannan, Sabina; Sultana, Seheli Zannat; Rahman, Mahbubur; Ahamed, M Shibbir; Sultana, Zinat Rezina (Journal of Bangladesh Society of Physiologist, 2009)
The aim of this study was to establish the standard weight of the normal spleen in Bangladeshi people. One hundred and twenty human cadavers of which eighty seven male and thirty three female were dissected to remove spleen with associated structures. Collected specimens were tagged with specific identification number, and divided into five groups according to age, sex and height of the individual. Gross and fine dissections were carried out after fixing the specimen in 10% formal saline solution. Weight of the spleen was measured by analytical balance and expressed in gram and findings of the study were compared with the findings of national and global studies. This cross sectional descriptive study was carried out in the Department of Anatomy of Mymensingh Medical College, Mymensingh. In this study maximum mean weight of spleen was 86.35 gram in male and 85.33 gram in female in 31 - 45 years age group. Minimum mean weight of spleen was 47.37 gram in male and 38.83 gram in female up to 15 years age group. The weight of spleen increases with age of the individual. Mean weight of spleen in male was 73.43 gram, which was higher than the mean weight of female spleen (59.17 gram). According to height of individual the mean weight of spleen was maximum 84.32 gram in 165.01 to 180 cm height group and minimum in 54.87 gram in up to 120 cm height group which indicate that weight of the spleen increases with height of the individual. In conclusion, the weight of the spleen depends on the age, sex and body height of the individual. Key Words: Spleen, Weight, Age, Height Â Â Â doi: 10.3329/jbsp.v3i0.1802 J Bangladesh Soc Physiol.2008 Dec;(3):71-78.